Philosophical foundations of property law - Penner, J. E. (James E.); Smith, Henry E. (Oxford : Oxford University Press, 2014)
This volume brings the concepts and doctrines of property law into the philosophy of property. It offers contributions from leading theorists of property law. The papers serve as introductions to many facets of philosophical work grounded in the law of property and as cutting edge contributions to the scholarly literature.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 2, 2013).
Keywords: Property -- Philosophy